Impact of MMP2 rs243865 and MMP3 rs3025058 Polymorphisms on Clinical Findings in Alzheimer’s Disease Patients - Vladimira Durmanova; Juraj Javor; Zuzana Parnicka; Gabriel Minarik; Agata Ocenasova; Barbora Vaseckova; Veronika Reznakova; Maria Kralova; Tomas Hromadka; Ivana Shawkatova (Mediators of Inflammation)
Alzheimer’s disease (AD) is a chronic neurodegenerative disease of the central nervous system with higher prevalence in elderly people. Despite numerous research studies, the etiopathogenesis of AD remains unclear. Matrix metalloproteinases (MMPs) are endopeptidases involved in the cleavage of extracellular matrix proteins and basement membrane compounds. In the brain, the pathological role of MMPs includes the disruption of the blood-brain barrier leading to the induction of neuroinflammation. Among various MMPs, MMP-2 and MMP-3 belong to candidate molecules related to AD pathology. In our study, we aimed to evaluate the association of MMP2 rs243865 and MMP3 rs3025058 polymorphisms with AD susceptibility and their influence on age at onset and MoCA score in patients from Slovakia. Both MMP gene promoter polymorphisms were genotyped in 171 AD patients and 308 controls by the PCR-RFLP method. No statistically significant differences in the distribution of MMP2 rs243865 (-1306 C>T) and MMP3 rs3025058 (-1171 5A>6A) alleles/genotypes were found between AD patients and the control group. However, correlation with clinical findings revealed later age at disease onset in MMP2 rs243865 CC carriers in the dominant model as compared to T allele carriers (CC vs. CT+TT: 78.44±6.28 vs. 76.36±6.39, p=0.036). The results of MMP3 rs3025058 analysis revealed that 5A/6A carriers in the overdominant model tended to have earlier age at disease onset as compared to other MMP3 genotype carriers (5A/6A vs. 5A/5A+6A/6A: 76.61±5.88 vs. 78.57±6.79, p=0.045). In conclusion, our results suggest that MMP2 rs243865 and MMP3 rs3025058 promoter polymorphisms may have influence on age at onset in AD patients.